(untitled) (Research, Society and Development, 2022)
The need to improve the construction processes of civil construction; demand of the agents involved to continually seek technological alternatives that provide more advantageous results. This article aims to comparatively analyze the constructive technology of internal coating with mechanical projection of mortar in relation to manual application, in terms of productivity, cost, adhesion resistance and quality. The results showed that the mechanical projection of the industrialized mortar brought significant efficiency gains, since even with the highest cost, it stood out in terms of adhesion resistance, productivity and a good final finish to receive ceramic coating. As a contribution, the sequence of analyzes and the comparison parameters used were adequate in the selection of the coating, being able to provide guidance in similar situations.